2000
DOI: 10.1007/s002590000341
|View full text |Cite
|
Sign up to set email alerts
|

Fever of unknown origin: prospective comparison of [18F]FDG imaging with a double-head coincidence camera and gallium-67 citrate SPET

Abstract: Gallium-67 citrate is currently considered as the tracer of first choice in the diagnostic workup of fever of unknown origin (FUO). Fluorine-18 2'-deoxy-2-fluoro-D-glucose (FDG) has been shown to accumulate in malignant tumours but also in inflammatory processes. The aim of this study was to prospectively evaluate FDG imaging with a double-head coincidence camera (DHCC) in patients with FUO in comparison with planar and single-photon emission tomography (SPET) 67Ga citrate scanning. Twenty FUO patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 18 publications
7
82
0
9
Order By: Relevance
“…• Evaluation of fever of unknown origin (FUO) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), including true FUO (defined according to the criteria of Durack and Street (44)), postoperative fever and recurrent sepsis, immunodeficiency (both induced and acquired)-related FUO, neutropenic fever, and isolated acute-phase inflammation markers (persistently raised C-reactive protein and/or erythrocyte sedimentation rate).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…• Evaluation of fever of unknown origin (FUO) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), including true FUO (defined according to the criteria of Durack and Street (44)), postoperative fever and recurrent sepsis, immunodeficiency (both induced and acquired)-related FUO, neutropenic fever, and isolated acute-phase inflammation markers (persistently raised C-reactive protein and/or erythrocyte sedimentation rate).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…Typically, studies retrospectively assessed nuclear imaging tests as second-or third-level examinations, performed after diagnostic workup that was not standardized in each study. Eight studies (19%) were prospective: 1 study adopted a standardized workup algorithm (28), and 3 studies specified mandatory preimaging tests (29)(30)(31) as selection criteria, one of which routinely performed thoracoabdominal contrast-enhanced CT (31). The average preimaging disease duration ranged from 5 to 41 wk.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Therefore, 67 Ga imaging has several disadvantages for patients: it is timeconsuming, must be repeated, and has a relatively high radiation burden. In a study of 58 patients with FUO, Meller et al showed that 67 Ga scintigraphy had a diagnostic yield nearly equivalent to that of 18 F-FDG PET (74). However, in that study, 18 F-FDG scanning was performed with a coincidence camera instead of a dedicated full-ring PET scanner, which is superior for PET.…”
Section: Imaging In Fuomentioning
confidence: 99%